A New Extension of Hardy-Hilbert's Inequality in the Whole Plane. (8th September 2016) - Yang, Bicheng; Chen, Qiang
Abstract : By the use of weight coefficients and Hermite-Hadamard's inequality, a new extension of Hardy-Hilbert's inequality in the whole plane with multiparameters and a best possible constant factor is given. The equivalent forms, the operator expressions, and a few particular inequalities are considered.